Migrating borders: Territorial rescaling and citizenship realignment in Europe - (:unkn) unknown (London: Routledge, 2019)
Migrating Borders explores the relationship between territory and citizenship at a time when the very boundaries of the political community come into question.Made up of an interdisciplinary team of social scientists, the book provides new answers to the age-old ‘question of nationalities’ as it unfolds in a particular context – the European multilevel federation – where polities are linked to each other through a complex web of vertical and horizontal relations. Individual chapters cover and compare well-known cases such as Catalonia, Kosovo and Scotland, but also others that often fall under the radar of mainstream analysis, such as the Turkish Republic of Northern Cyprus or the Roma. At a time of heightened uncertainty surrounding the European integration project, the book offers an invaluable theoretical and empirical compass to navigate some of the most pressing issues in contemporary European politics.Exploring what happens to citizenship when borders ‘migrate’ over people, Migrating Borders will be of great interest to scholars of Ethnic and Migration Studies, European Politics and Society, Nationalism, European Integration and Citizenship. This book was originally published as a special issue of Ethnopolitics.
Keywords: Nationalism; citizenship; Europe; migration; comparative politics